Analisis Jangkauan Pelayanan Fasilitas Kesehatan di Kecamatan Bengkalis - Deanty, Ilfa (JURNAL BUANA, 2025)
Access to services can be measured geographically (spatial factors) based on area and distance, with this measurement a comparison is obtained between the total population in an area and the number of health facilities available. The location distribution of health service centers in Bengkalis District can be placed in the right location by considering the existing spatial organization with the aim of making it more efficient and easily accessible by the community. The construction of health facilities in Bengkalis District has not been evenly distributed and has not taken into account the distribution of community settlement patterns. This study aims to describe and provide information on the Outreach of Health Facilities in Bengkalis District. This research is quantitative descriptive. The unit of analysis for this study was the Puskesmas in Bengkalis District, namely the Sungai Alam Health Center and the Pematang Duku Health Center. The analysis technique used is Buffer Analyst. This study found: (a) The service coverage of the Sungai Alam Health Center and Pematang Duku Health Center based on the results of the buffer was still very poor with the percentage of served areas of 10.93% and 14.69%. (b) The number of served population based on buffer results at the Sungai Alam Health Center, namely 8,211.77 residents and 66,870.23 unserved residents, while the Pematang Duku Health Center was able to serve 2,070.43 residents and 11,993.57 residents who were not served.